2015
DOI: 10.1186/s13045-015-0156-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the immunodeficiency of a mouse strain by tumor engraftments

Abstract: BackgroundThe mouse is an organism that is widely used as a mammalian model for studying human physiology or disease, and the development of immunodeficient mice has provided a valuable tool for basic and applied human disease research. Following the development of large-scale mouse knockout programs and genome-editing tools, it has become increasingly efficient to generate genetically modified mouse strains with immunodeficiency. However, due to the lack of a standardized system for evaluating the immuno-capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 35 publications
3
36
0
1
Order By: Relevance
“…However, in the Rag-2 knockout (KO) mice used by Chevez-Barrios et al (2000), the animals were intravitreally injected with Y79 cells in a similar manner as in our experiment, but the mice already developed metastases 4 weeks after the injection (Chevez-Barrios et al, 2000). These results are consistent with those of other groups, who could show that metastasization metastasesin Rag-2 KO mouse models are stronger than in nude mice for several human cancer xenografts like sarcoma (Nanni et al, 2010), breast cancer (Nanni et al, 2012) or adenocarcinoma (Ye et al, 2015). This should be considered when choosing a model.…”
Section: Discussionsupporting
confidence: 93%
“…However, in the Rag-2 knockout (KO) mice used by Chevez-Barrios et al (2000), the animals were intravitreally injected with Y79 cells in a similar manner as in our experiment, but the mice already developed metastases 4 weeks after the injection (Chevez-Barrios et al, 2000). These results are consistent with those of other groups, who could show that metastasization metastasesin Rag-2 KO mouse models are stronger than in nude mice for several human cancer xenografts like sarcoma (Nanni et al, 2010), breast cancer (Nanni et al, 2012) or adenocarcinoma (Ye et al, 2015). This should be considered when choosing a model.…”
Section: Discussionsupporting
confidence: 93%
“…The diagnosis of HCC was confirmed by histologic analysis in all cases. HCC tissues were transplanted into NOD/SCID/IL2rg −/− (NSI) mice that were sourced from Li’s lab (1517). Primary HCC tumors were placed in RPMI 1640 in an ice bath.…”
Section: Methodsmentioning
confidence: 99%
“…32 Here, we generated human NSCLC PDX mice by subcutaneously or intravenously implanting dissected primary tumor masses or cell suspensions that could be serially transplanted and engrafted in NSI mice. Immunohistochemistry results showed that HLA C NSCLC cells from a patient (patient P2) that had been engrafted in the lungs of NSI mice expressed E-cadherin, but not vimentin, during both the first and second passages after transplantation (Fig.…”
Section: Pdx Models Retained Molecular Phenotype Of Nsclc Cellsmentioning
confidence: 99%